Effect of Job Insecurity, Soft Skill, Hard Skill and Work Engagement on Innovative Work Behavior - Francisco Fernando Graham Ginsu; Willem JF A Tumbuan; Irvan Trang (International Journal on Economics, Finance and Sustainable Development, 2022)
This study aims to analyze the effect of Job Insecurity, Soft Skills, Hard Skills and Job Involvement on Employee Innovative Work Behavior (Study on Employees of PT. PLN Persero UP3 Pamekasan). Respondents in this study amounted to 95 employees who are permanent employees in PT PLN (Persero) UP3 Pamekasan. This study uses multiple linear regression analysis. The partial test results show that the Job insecurity variable has no significant effect on the innovative behavior of PT. PLN (Persero) UP3 Pamekasan employees, the Soft skill variable has a significant effect on the innovative behavior of PT. PLN (Persero) UP3 Pamekasan employees, the Hard skill variable has a significant effect on behavior. innovative employees of PT. PLN (Persero) UP3 Pamekasan, the variable of work involvement has a significant effect on the innovative behavior of employees of PT. PLN (Persero) UP3 Pamekasan. Companies should need to build maximum involvement of all employees to continuously improve their hard skills and soft skills. Training in each section is a necessity with a level of intensity, content and context that is adjusted to the key performance indicators of each employee.